Kajian Hukum Terhadap Anak Yang Melakukan Tindak Pidana Narkotika Dalam Perspektif Kriminologi Studi di Polresta Deli Serdang - Rajarif Syah Akbar Simatupang; Abdul Hakim Siagian; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to find out the causal factors, modus operandi and prevention efforts of children who commit narcotics crimes in the perspective of criminology in Deli Serdang Police.. This research uses normative legal methods by using a normative juridical approach (Legal Reseach) to obtain secondary data conducted by research and interview, to obtain primary data through library materials and invitees. The results showed that the legal study of children who commit narcotics crimes in the perspective of criminology, based on indicators are as follows: First, the causative factors of narcotics crimes committed by children are internal factors (factors obtained by children from the family and from within the child themselves and external factors (factors obtained from the environment, association, economic situation and cultural influences abroad). Second, the modus operandi carried out by children in committing narcotics crimes is carried out in groups and individuals, the child can use narcotics by lying to parents in terms of material (pocket money) to commit criminal acts of theft. Third, the efforts and prevention so that narcotics crimes committed by children are not repeated through the existence of legal policies consisting of repressive and preventive efforts by the Deli Serdang Police.